Meningkatkan Loyalitas Guru: Work Life Balance, Lingkungan Kerja Fisik, dan Kepuasan Kerja - Adiantara, M. Agung Dwi; Cahyadi, Irwan; Yuliana, Ika; Makiah, Makiah; Marlina, Febria Nurmelia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the factors influencing the loyalty of honorary teachers at the Nurul Haramain Putri NWDI Narmada Islamic Boarding School. Teacher loyalty is essential for the sustainability of educational institutions, yet it is often challenged by difficulties in maintaining work–life balance, limited physical facilities, and varied levels of job satisfaction. The objective of this research is to analyze the effects of work–life balance, physical work environment, and job satisfaction on teacher loyalty, both individually and collectively. A quantitative descriptive method was employed, with a sample of 60 respondents selected purposively from a population of 200 honorary teachers. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression with SPSS 22. The results reveal that work-life balance has a positive and significant effect on teacher loyalty, while the physical work environment and job satisfaction show positive but insignificant effects. These findings suggest that improving work-life balance should be prioritized to strengthen teacher loyalty, while improvements in physical facilities and job satisfaction remain necessary as supporting factors.